Decision Support System for New Employee Recruitment Using Profile Matching and Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) Method - Elsi Titasari Br Bangun; Retantyo Wardoyo; Yudha Islami Sulistya; Bayu Anugerah Putra; Fauzan Azim (JRST (Jurnal Riset Sains dan Teknologi), 2025)
This research focuses on the challenges of recruiting new employees at Perumdam Tirta Siak Pekanbaru, which often involves time-consuming procedures and is prone to subjective bias. The main objective is to develop a decision support system using the profile matching and Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) methods to enhance the efficiency and effectiveness of HRD in selecting the best candidates. Profile matching is used to assess applicant competency with company criteria, while PROMETHEE determines the priority order of candidates. The data collected and analyzed includes assessment criteria and user feedback. The conclusion confirms the effectiveness of the system in setting assessment parameters accurately and minimizing subjective bias. The system shows high flexibility in adapting to changing assessment parameters and candidates. Test results show the system is capable of producing consistent and reliable employee ratings, making it a valuable tool in recruitment at Perumdam Tirta Siak. Its implementation is expected to bring the company closer to its long-term strategic goals and strengthen the decision-making process for recruiting new employees.